2015
DOI: 10.1111/iere.12128
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, Imperfect Competition, and the U.S. Abortion Market

Abstract: The market for abortion in the U.S. has become increasingly concentrated in recent years, while many states have tightened abortion regulations aimed at providers. Using unique data on abortion providers I estimate an equilibrium model of demand, price competition, entry and exit, which captures the effect of regulation on the entire market. The estimates show that regulations played an important role in determining the structure and evolution of the abortion market. Counterfactual simulations reveal increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Studies in our review tended to agree that TRAP laws were associated with a decrease in provider availability, with one reporting a loss of 46% of all Texas providers in the year following HB2 enforcement 5. The relationship between policies and providers was particularly central to one analysis20 that was principally concerned with the behaviour of the abortion market in response to regulations. This study reported that TRAP laws decreased market entry rates for clinics and increased the cost of procedures by approximately 10%.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Studies in our review tended to agree that TRAP laws were associated with a decrease in provider availability, with one reporting a loss of 46% of all Texas providers in the year following HB2 enforcement 5. The relationship between policies and providers was particularly central to one analysis20 that was principally concerned with the behaviour of the abortion market in response to regulations. This study reported that TRAP laws decreased market entry rates for clinics and increased the cost of procedures by approximately 10%.…”
Section: Resultsmentioning
confidence: 94%
“…Depending on the analysis, the magnitude of this effect ranged from a 6.8% decline in the abortion rate among women aged 18–30 years,21 to a 13% decline in the abortion rate among all women of childbearing age (15–44 years),5 to a 72% decrease in the abortion rate among women presenting at or after 16 weeks’ gestation 18. In contrast, one study in this subgroup found no effect of TRAP laws on abortion demand,19 and one reported a potential increase in abortions following TRAP legislation 20. Both of these studies concluded that demand-side policies (particularly parental consent laws) play a more significant role than supply-side policies in explaining the contemporary decline in abortion rates 19 20…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…After knowing if they became pregnant, they decide whether to work part-time, full-time, or not 1 Henshaw et al (2009), Joyce et al (2009), and Dennis et al (2009) summarize the findings of the literature for Medicaid funding restrictions, mandatory counseling requirements and parental consent requirements, respectively. Beauchamp (2012) has shown that, between 1991 and 2005, supply-side regulation led to an annual average decrease of 5.86% in the number of counties with a provider.…”
mentioning
confidence: 99%
“…For instance, Cook et al (1999) find that, among eligible women, 37% of the pregnancies that would have ended in abortion were carried to term, a result that is consistent with the later analysis of Morgan and Parnell (2002). Finally, with respect to the supply-side restrictions, Beauchamp (2012) estimates a dynamic model of entry and exit of providers to the abortion market. He finds that restrictions imposed on providers lead to the concentration of abortion services in fewer and bigger abortion clinics, decreasing the number of providers and thus access to abortion services.…”
mentioning
confidence: 99%